PEMBERDAYAAN KADER REMAJA DALAM PEMANTAUAN STATUS GIZI UNTUK PENCEGAHAN OBESITAS DI SMP KABUPATEN SOPPENG - Yusnitasari, Andi Selvi; Mansur, Marini Amalia; Rahmadani, Suci; Damayanti, Handini; Ramadhani, Andi Tis’a; Hisan, Khaeratun (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The health problems experienced by adolescents today are the triple burden of malnutrition, namely undernutrition, excess nutrition (obesity), and iron deficiency anemia. School is an environment that has an important role in conveying health information to adolescents. Therefore, it is necessary to empower youth cadres in schools so that nutritional status monitoring can be carried out independently and periodically. Community service activities were carried out at SMPN 1 Soppeng by involving 10 students as training participants. After being trained to measure nutritional status, students practice measuring other students. The measurement results illustrate that the average nutritional status of adolescents is normal (44%). However, the prevalence of wasting is quite high, reaching 32% and the prevalence of obesity is up to 24%. Therefore, the school needs to measure the nutritional status of students on a regular basis so that interventions can be carried out to improve the nutritional status of students so that healthy and achieving students can be produced